Enhancing the framework for financial assistance in the field of physical education and sports through the collaboration of public and private sectors - Altushkin T.I.; Naboychenko E.S.; Knyazeva E.G. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to validate the framework for financial backing of physical fitness and sports through a combination of public and private involvement. Methods and structure of the study. The analytical models of contemporary economic and social phenomena were examined using a combination of system-based, functional, and comparative analysis techniques. Results and conclusions. The sustainable advancement of physical culture and sports at the national level necessitates a concentration on the creation and implementation of novel ideas, while also fostering an environment that encourages private initiatives. A balanced approach to funding, combining both public and private sources, is crucial in this area. The financial and organizational assistance provided by national corporations to children’s sports and specialized sports should be endorsed by the public and the government. The expenses for the ongoing maintenance and implementation of investment projects related to sports facilities should be factored into the corporate social responsibility evaluation, financial health, and taxation of companies. The financial and administrative decisions aimed at fostering the growth of physical culture and sports in the regions where national corporations operate should be met with positive feedback. The strategic approach involves interdepartmental and intersectoral collaboration, the unification of efforts between federal and regional government bodies and local authorities, and the coordination of public and professional organizations in the areas of legislative, economic, and financial support for the advancement of physical culture and sports.